Development and Application of Sub-Mitochondrial Targeted Ca2 + Biosensors - Waldeck-Weiermair, Markus; Gottschalk, Benjamin; Madreiter-Sokolowski, Corina T.; Ramadani-Muja, Jeta; Ziomek, Gabriela; Klec, Christiane; Burgstaller, Sandra; Bischof, Helmut; Depaoli, Maria R.; Eroglu, Emrah; Malli, Roland; Graier, Wolfgang F. (Frontiers in Cellular Neuroscience, 2019)
Mitochondrial Ca2+ uptake into the mitochondrial matrix is a well-established mechanism. However, the sub-organellar Ca2+ kinetics remain elusive. In the present work we identified novel site-specific targeting sequences for the intermembrane space (IMS) and the cristae lumen (CL). We used these novel targeting peptides to develop green- and red- Ca2+ biosensors targeted to the IMS and to the CL. Based on their distinctive spectral properties, and comparable sensitivities these novel constructs were suitable to visualize Ca2+-levels in various (sub)compartments in a multichromatic manner. Functional studies that applied these new biosensors revealed that knockdown of MCU and EMRE yielded elevated Ca2+ levels inside the CL but not the IMS in response to IP3-generating agonists. Knockdown of VDAC1, however, strongly impeded the transfer of Ca2+ through the OMM while the cytosolic Ca2+ signal remained unchanged. The novel sub-mitochondrially-targeted Ca2+ biosensors proved to be suitable for Ca2+ imaging with high spatial and temporal resolution in a multichromatic manner allowing simultaneous measurements. These informative biosensors will facilitate efforts to dissect the complex sub-mitochondrial Ca2+ signaling under (patho)physiological conditions.